Effects of white noise on procedural pain-related cortical response and pain score in neonates: A randomized controlled trial - Xuyan Ren; Li Li; Siya Lin; Chunxia Zhong; Bin Wang (Elsevier, 2022)
Objectives: To evaluate the effects of white noise on pain-related cortical response, pain score, and behavioral and physiological parameters in neonates with procedural pain. Methods: A double-blind, randomized controlled trial was conducted. Sixty-six neonates from the Neonatal Intensive Care Unit in a university-affiliated general hospital were randomly assigned to listen to white noise at 50 dB (experimental group) or 0 dB (control group) 2 min before radial artery blood sampling and continued until 5 min after needle withdrawal. Pain-related cortical response was measured by regional cerebral oxygen saturation (rScO2) monitored with near-infrared spectroscopy, and facial expressions and physiological parameters were recorded by two video cameras. Two assessors scored the Premature Infant Pain Profile-Revised (PIPP-R) independently when viewing the videos. Primary outcomes were pain score and rScO2 during arterial puncture and 5 min after needle withdrawal. Secondary outcomes were pulse oximetric oxygen saturation (SpO2) and heart rate (HR) during arterial puncture, and duration of painful expressions. The study was registered at the Chinese Clinical Trial Registry (ChiCTR2200055571). Results: Sixty neonates (experimental group, n = 29; control group, n = 31) were included in the final analysis. The maximum PIPP-R score in the experimental and control groups was 12.00 (9.50, 13.00), 12.50 (10.50, 13.75), respectively (median difference −0.5, 95% CI −2.0 to 0.5), and minimum rScO2 was (61.22 ± 3.07)%, (61.32 ± 2.79)%, respectively (mean difference −0.325, 95% CI −1.382 to 0.732), without significant differences. During arterial puncture, the mean rScO2, HR, and SpO2 did not differ between groups. After needle withdrawal, the trends for rScO2, PIPP-R score, and facial expression returning to baseline were different between the two groups without statistical significance. Conclusion: The white noise intervention did not show beneficial effects on pain-related cortical response as well as pain score, behavioral and physiological parameters in neonates with procedural pain.